Identification of Phenolic Compounds Content in Tinospora crispa Stem Decoction by FTIR and UV-Visible Spectrophotometry - Elisabet Sa Wulo; Yunike Kurnia Unda; Suparno (Postgraduate, University of Mataram, 2025)
Phenolics are compounds that have a hydroxyl (OH) group attached to an aromatic ring, and are known for various health benefits such as antioxidant, antimicrobial, and anti-inflammatory properties. This study aims to measure the total phenolic content and characterize the functional groups in Tinospora crispa stem extract using a decoction method, as well as evaluate its potential as a source of bioactive compounds. Extraction was performed by boiling dried Tinospora crispa stems in water. Total phenolic content was quantified using UV-Vis spectrophotometry (λ = 765 nm) via the Folin-Ciocalteu reaction, with a gallic acid calibration curve (R² = 0.998). Functional group analysis was conducted using FTIR (4000–400 cm⁻¹). The extract showed high phenolic content (384.909 mg GAE/g), supported by the identification of characteristic functional groups such as O-H (3255.55 cm⁻¹), C=C (2121.59 cm⁻¹), and C-O (1261.45 cm⁻¹) in the FTIR spectrum. These groups are associated with the presence of bioactive compounds such as phenolics. Therefore, Tinospora crispa has potential as a source of phenolic compounds, one of which can be obtained using the decoction method.